Låglastdrift vid dynamisk positionering offshore - En studie gällande maskintekniska åtgärder som två motortillverkare ämnar att tillse marknaden - Backlund, Jeff; Persson, Lars (My University, 2015)
The majority of the offshore installations operating in dynamic positioning (DP) are continuously running in low load operation. Diesel engines running on low load have low efficiency and high specific fuel oil consumption (SFOC). The questions in the study shall give an answer to if engine manufacturers have any technical solutions to the problem. This study is to be regarded as a case study, where two engine manufacturers are interviewed about available technical solutions to increase efficiency at low load operation and if research and development occurs in this area. Interviews with two of the market leading engine manufactures in offshore industry are performed to generate the most reliable information from companies with expertise in this area. The study is focusing on semi-submersible platforms as these often operate continuously in DP operation which is common in the offshore industry. The result of the study indicates that engine manufactures are unanimous about the fact that there are problems with low load operation to consider and that measures should be taken. The two engine manufacturers decided to develop two different solutions to the problem with low load operation. MAN has chosen only to produce newly built engine solutions and Wärtsilä is developing a retrofit to supply the existing market. Today there is no solution on the market that can increase the efficiency of existing engines. For new construction, the solutions MAN presents can be used.
Keywords: Annan teknik; Maskinteknik; Transport; Other Engineering and Technologies; Mechanical Engineering; Transport